2023
DOI: 10.1021/acs.est.2c07862
|View full text |Cite
|
Sign up to set email alerts
|

A New Electron Shuttling Pathway Mediated by Lipophilic Phenoxazine via the Interaction with Periplasmic and Inner Membrane Proteins of Shewanella oneidensis MR-1

Abstract: Although it has been established that electron mediators substantially promote extracellular electron transfer (EET), electron shuttling pathways are not fully understood. Here, a new electron shuttling pathway was found in the EET process by Shewanella oneidensis MR-1 with resazurin, a lipophilic electron mediator. With resazurin, the genes encoding outer-membrane cytochromes (mtrCBA and omcA) were downregulated. Although cytochrome deletion substantially reduced biocurrent generation to 1−12% of that of wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…For instance, S. oneidensis MR‐1, a Gram‐negative bacterium, excels in extracellular electron transfer facilitated by specialized outer membrane cytochromes for direct contact transfer. [ 35 ] On the contrary, B. subtilis , a Gram‐positive bacterium found in soil and the gastrointestinal tract produces flavins that serve as effective electron shuttles. The flavins can transfer electrons to extracellular electron acceptors, enabling B. subtilis to participate in redox reactions and potentially interact with external electrodes for relatively long‐range electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, S. oneidensis MR‐1, a Gram‐negative bacterium, excels in extracellular electron transfer facilitated by specialized outer membrane cytochromes for direct contact transfer. [ 35 ] On the contrary, B. subtilis , a Gram‐positive bacterium found in soil and the gastrointestinal tract produces flavins that serve as effective electron shuttles. The flavins can transfer electrons to extracellular electron acceptors, enabling B. subtilis to participate in redox reactions and potentially interact with external electrodes for relatively long‐range electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that PCA can enhance EET capacity in both Escherichia coli and MR-1 species. 10,29 In this study, a gene cluster consisting of seven related genes, phzA1-G1, was successfully transferred from P. aeruginosa into the MR-1 genome under the control of an arabinose-inducible promoter (Figure 3A). The cargo gene was replaced with an 8.2 kb fragment containing the PCA synthesis gene cluster in p-INTEGRATE.…”
Section: Insertion Of Pca Synthesis Genes Using the Inte-grate Systemmentioning
confidence: 95%
“…When SW@CdS was used, it also changed to the original color of the photocatalyst (yellow), which suggests a microbial electron shuttling process and the successful formation of an anaerobic environment. 53 The quantity of the generated H 2 O 2 for the SW@CdS and CdS photocatalysts was determined by iodometry. The amount of H 2 O 2 produced after four-hour illumination was 0.96 μM, which was slightly lower than that of chemosynthetic CdS (1.61 μM) and much lower than the reported value for photocatalysts used for producing hydrogen peroxide (Fig.…”
Section: Performance Of Photocatalytic Co 2 Reductionmentioning
confidence: 99%